Reading readiness activities for educable mentally retarded children - Doroliat, Anacleta (Bisnar) 1928- (s.n.], 1968)
This is an observation of the pre-school mentally retarded children at the Foundation for Mentally Retarded Children and at the Special Child Study Center. The study concludes that the reading readiness activities for educable mentally retarded children facilitate learning reading and can lead to favorable attitudes toward other areas of learning.